2023
DOI: 10.1136/ard-2023-223974
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following SARS-CoV-2 infection in individuals with and without inflammatory rheumatic diseases: a Danish nationwide cohort study

Abstract: ObjectiveIn a setting with an extensive SARS-CoV-2 test strategy and availability of effective vaccines, we aimed to investigate if patients with inflammatory rheumatic diseases (IRD) face greater risk of contracting SARS-CoV-2 and have a worse prognosis of increased risk of hospitalisation, assisted ventilation and death compared with the general population.MethodsThis was a nationwide, population-based register study that compared outcomes of SARS-CoV-2 infection in Danish patients with IRD (n=66 840) with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…In the nationwide Greek cohort study conducted in the first half of 2022, patients with rheumatoid arthritis who were infected with SARS-CoV-2 had an elevated risk of hospitalization (odds ratio [OR] = 2.02, 95% CI: 1.79-2.27) and death (OR = 1.73, 95% CI: 1.36-2.20) as compared to controls [24]. Additionally, based on the data from the Danish national registers, the risk of hospitalization of patients with RMDs in the SARS-CoV-2 Omicron era decreased compared to the pre-Omicron period; however, it remained higher than in the general population [25]. The risk of death decreased substantially after the Omicron variant became the dominating strain; however, again, it was substantially higher compared to non-RMD controls [25].…”
Section: Risks Associated With Covid-19mentioning
confidence: 90%
See 2 more Smart Citations
“…In the nationwide Greek cohort study conducted in the first half of 2022, patients with rheumatoid arthritis who were infected with SARS-CoV-2 had an elevated risk of hospitalization (odds ratio [OR] = 2.02, 95% CI: 1.79-2.27) and death (OR = 1.73, 95% CI: 1.36-2.20) as compared to controls [24]. Additionally, based on the data from the Danish national registers, the risk of hospitalization of patients with RMDs in the SARS-CoV-2 Omicron era decreased compared to the pre-Omicron period; however, it remained higher than in the general population [25]. The risk of death decreased substantially after the Omicron variant became the dominating strain; however, again, it was substantially higher compared to non-RMD controls [25].…”
Section: Risks Associated With Covid-19mentioning
confidence: 90%
“…Patients with RMDs have remained at elevated risk of hospitalization due to COVID-19 since the beginning of the pandemic [23]. Even in the era of SARS-CoV-2 Omicron dominance and increased vaccination rates, RMD remains a crucial risk factor for hospitalization and death [24][25][26]. In the nationwide Greek cohort study conducted in the first half of 2022, patients with rheumatoid arthritis who were infected with SARS-CoV-2 had an elevated risk of hospitalization (odds ratio [OR] = 2.02, 95% CI: 1.79-2.27) and death (OR = 1.73, 95% CI: 1.36-2.20) as compared to controls [24].…”
Section: Risks Associated With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies attempting to investigate this association are limited by a lack of comparator groups, recall bias, and information bias 16,18,19,21,22 . Patients with SRD can benefit from vaccination: data suggest this group may be at increased risk of hospitalization, mechanical ventilation, and death from COVID‐19, 23,24 and a recent population‐based study found the risk of severe COVID‐19 infection has persisted since the emergence of the Omicron variant 25 . As vaccination coverage expands among individuals with SRD and approaches rates in the general population, 25 an accurate estimation of flare risk following immunization is important for informing both public health guidance and individual patient care.…”
Section: Introductionmentioning
confidence: 99%